Chronic Obstructive Pulmonary Disease : A Systemic Inflammatory Disease - Nakamura, Hiroyuki; Aoshiba, Kazutetsu (Springer Singapore : Imprint: Springer, 2017)
This book considers chronic obstructive pulmonary disease (COPD) not as a simple inflammation of the lung but as a systemic inflammatory disease. Beginning with epidemiological studies, etiology, diagnosis and treatment, it elaborates further, illustrating some comorbidities and associations with other respiratory diseases. As such it provides numerous improved and more comprehensive treatment methods, including drug therapies as well as some non-drug therapies. There are also chapters describing the pathogenesis, genetic abnormalities and newly discovered pathogenetic mechanisms that are expected to be studied further in the future. Edited and written by pioneering researchers, each chapter summarizes the latest trends, describes future prospects and explores the unresolved and critical questions. Chronic Obstructive Pulmonary Disease - A Systemic Inflammatory Disease is a valuable resource to beginning researchers, physicians engaged in clinical practice, supervisors, and basic researchers whose work includes COPD.
Keywords: Medicine.; Respiratory organs -- Diseases.; elektronické knihy; electronic books